2019
DOI: 10.3390/cancers11010110
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Electric Fields (TTFields) Activate Cav1.2 Channels in Human Glioblastoma Cells

Abstract: Tumor treating fields (TTFields) represent a novel FDA-approved treatment modality for patients with newly diagnosed or recurrent glioblastoma multiforme. This therapy applies intermediate frequency alternating electric fields with low intensity to the tumor volume by the use of non-invasive transducer electrode arrays. Mechanistically, TTFields have been proposed to impair formation of the mitotic spindle apparatus and cytokinesis. In order to identify further potential molecular targets, here the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 64 publications
2
72
0
Order By: Relevance
“…49 This suggests that stalled replication fork stabilization confers resistance to replication stress-inducing chemotherapeutics but because of the general suppression of a host of genes and proteins involved in replication fork maintenance and stability, checkpoint control and DNA repair pathways, TTFields exposure may overcome such resistance. Indeed the results herein provide a rationale for the additive to synergistic effects of TTFields seen in earlier preclinical reports 10,[12][13][14][15] with chemotherapeutic drugs such as paclitaxel, cisplatin, gemcitabine, doxorubicin, 5-FU, cyclophosphamide, DTIC, and Irinotecan which are known to primarily increase replication stress but not directly affect mitosis. [7][8][9][10][11] DNA replication is a mandatory and prerequisite step for mitosis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…49 This suggests that stalled replication fork stabilization confers resistance to replication stress-inducing chemotherapeutics but because of the general suppression of a host of genes and proteins involved in replication fork maintenance and stability, checkpoint control and DNA repair pathways, TTFields exposure may overcome such resistance. Indeed the results herein provide a rationale for the additive to synergistic effects of TTFields seen in earlier preclinical reports 10,[12][13][14][15] with chemotherapeutic drugs such as paclitaxel, cisplatin, gemcitabine, doxorubicin, 5-FU, cyclophosphamide, DTIC, and Irinotecan which are known to primarily increase replication stress but not directly affect mitosis. [7][8][9][10][11] DNA replication is a mandatory and prerequisite step for mitosis.…”
Section: Discussionmentioning
confidence: 57%
“…[7][8][9][10][11][12] TTFields also target the calcium channel Cav1.2, and combinations of calcium antagonists, such as benidipine enhance glioma cell killing. 13 Furthermore, AMPK-dependent autophagy, which occurred after cells had undergone mitosis in response to aneuploidy and ER (Endoplasmic reticulum) stress, was identified as a survival mechanism upon TTFields exposure and serves as a druggable resistance mechanism to TTFields. 14 These preclinical results cannot be explained by the interruption of mitosis, which suggests that there are other mechanisms by which TTFields used in combination with different chemotherapeutic agents elicit additive or synergistic cell killing.…”
Section: Translational Significancementioning
confidence: 99%
“…TTFields exposure was also shown to induce calcium signals in a dose-dependent manner by activating L-type calcium channels (CACNA1C) in GBM cells (Neuhaus et al 2019). Those results suggest that the pharmacological blockade of calcium channels with agents like benidipine and nifedipine may augment the effects of TTFields exposure.…”
Section: Ttfields Induced Mechanisms Of Actionmentioning
confidence: 77%
“…Indeed, a study using two different human glioblastoma lines revealed cell line-specific responses to TTFields. 8 In addition, the application of TTFields may delay DNA damage repair following radiation treatment, leading to the emergence of therapeutic resistance. 8,13 All these conditions suggest that the therapeutic efficacy of TEFTS may vary between patients and in different stages of tumor, which necessitates the need to adjust the intensity and frequency of TTFields during the course of treatment.…”
Section: Safety Of Teftsmentioning
confidence: 99%
“…4,6,7 Finally, the electric fields therapy is recently reported to work through a cell line-specific mechanism to stimulate Ca 2+ entry via Cav1.2, which culminates in cell cycle arrest, DNA degradation, and cell death. 8 Intriguingly, the TTfields preferentially target tumor cells but leave the normal cells intact, rendering it a promising therapy for cancers.…”
Section: Introductionmentioning
confidence: 99%